COVID-19 pandemic impact on dentists in Latin America's epicenter: São-Paulo, Brazil - Olegário da Costa, Isabel (My University, 2021)
The state of São Paulo, Brazil, where more than 94.000 dentists are currently registered, has become the epicenter of COVID-19 in Latin America. The aim of this cross-sectional study was to evaluate the impact of COVID-19 pandemic on dentists in this state. A semi-structured questionnaire was sent via e-mail to 93.280 dentists with active registration in the Dental Council of São Paulo (CROSP). The impact of COVID-19 pandemic was assessed through questions related to demographic, socioeconomic, dental practice characteristics and personal protective equipment (PPE) use. Ordinal logistic regression analysis was performed to investigate the association between all the variables (p<0.05). Over 8 days, 2113 responses were received. Only 26.52% of the sample reported a low-income reduction (from 0-10%), while the majority of dentists reported a more negative financial impact, 35.6% with a reduction of more than 50% of their monthly income. Dentists who worked in the private sector and at the capital had a greater financial impact when compared to those of the public sector and countryside of the state (p<0.05). Furthermore, about 83% reported not having received any specific training to control the transmission of coronavirus in the health area. This study provides evidence of the negative impact of the COVID-19 pandemic on the routine of dentists in the state of São Paulo, Brazil. Hopefully, this study will help dental and other health care professionals to better understand the consequences of disease in dental settings and strengthen preparedness throughout the dental health care system.
Keywords: COVID and Dentistry; Employment